2012
DOI: 10.2224/sbp.2012.40.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Communal and Exchange Relationships and the Effects of Norms on Internet Participation

Abstract: In recent years, there has been a significant rise in the popularity of Web 2.0 applications. Our purpose was to examine the behaviors of Internet users. Voluntary participants (N = 691) were recruited through banners posted on a leading commercial website in Taiwan and were randomly allocated to 7 groups. The between-participants experimental design included 3 forms of payment crossed with 2 levels of payment, and a control condition with no payment. We found that behaviors on the Internet are linked to norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Regarding the willingness to help, they replicated the original finding that in the monetary payment condition, there was a positive relationship between the willingness to help and the payment level. However, while Heyman & Ariely (2004) argued that the payment level would have the same effect when the payment form was monetized goods (i.e., soap with a price tag), Liu et al (2012) failed to find support for payment level affecting monetized goods. Though their research design was different from the original studies, their findings raised doubts regarding the robustness and generalizability of Heyman & Ariely (2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the willingness to help, they replicated the original finding that in the monetary payment condition, there was a positive relationship between the willingness to help and the payment level. However, while Heyman & Ariely (2004) argued that the payment level would have the same effect when the payment form was monetized goods (i.e., soap with a price tag), Liu et al (2012) failed to find support for payment level affecting monetized goods. Though their research design was different from the original studies, their findings raised doubts regarding the robustness and generalizability of Heyman & Ariely (2004).…”
mentioning
confidence: 99%
“…Second, a previous study with a similar experimental paradigm found contradictory results. Following Heyman & Ariely (2004), Liu et al (2012) investigated the relative effectiveness of three payment forms (cash, soap, and soap with a price tag) with two different payment levels (low vs. medium) in encouraging individuals to participate in and take time to respond to a short survey. They failed to find support for effort level change depending on the level of the cash payment.…”
mentioning
confidence: 99%